Pengaruh Pengembangan Klinik Sanitasi Puskesmas Minggir Terhadap Peningkatan Pengetahuan dan Mutu Lingkungan Rumah Pasien - Siti Maryati; Muryoto Muryoto; Indah Werdiningsih (Poltekkes Kemenkes Yogyakarta, 2013)
Eventhough the prevention efforts for communicable diseases through sanitation clinic has beenimplemented for a long time, it is still not optimal. As an example, the average number of patientsin a month who come for counseling in the sanitation clinic of the Community Health Center(Puskesmas) of Minggir is only four. Meanwhile, in 2011, at the same puskesmas, the number ofcases of communicable diseases such as diarrhoea, acure respiratory infection (ARI) and dengue haemorrhagic fever (DHF) were still found at high level. Therefore, it is argued that theexisting sanitation clinic should be more developed. The study was aimed to know whether theknowledge and the quality of house condition of the patients as well as the revenue of sanitationclinic can be increased by developing the activity of the sanitation clinic itself, by conducting apre-experiment study which employed one group pre-test and post-test design. The number ofsample size was 36 people, which were consisted of 20 diarrhoea patients, 15 ARI patients and20 DHF patient with his neighbours. The collection of pre-test and post-test data were separatedby the activity of the counseling and home visit whose purpose was to improve the environmental condition of the patients, by means of chlorine diffuser installation and fly sticker application, for diarrhoea cases; advice of avoiding smoke from kitchen and the rearrangement ofventilation, for ARI cases; and the distribution of Abate and mosquito trap installation, for DHFcases. Statistical examination on the data by using t-test at 95 % significancy level showed thatthe counseling raised the knowledge of patients of the environmentally based diseases, and thehome visit could also improving the quality of patients’ houses, which was indicated by the reduction of the MPN E. Coli, the fly density and the ovitrap index. In addition, the increase of revenue from the sanitation clinic was influenced, as well.